Your answer should be 1200 inches cubed
Answer:
Yes it satisfies the equation
Step-by-step explanation:
Let, P(x,y) = (-9,-4)
Then, x = -9
y = -4
if we use this value in the equation, we will get L.S = R.S ;(-4 = -9 + 5)
So, the point satisfies the equation
Hope you have understood this
Pls mark my answer as the brainliest
The correct answer is = because 4/6 simplifies to 2/3
Checking the <span>discontinuity at point -4
from the left f(-4) = 4
from the right f(-4) = (-4+2)² = (-2)² = 4
∴ The function is continues at -4
</span>
<span>Checking the <span>discontinuity at point -2
from the left f(-2) = </span></span><span><span>(-2+2)² = 0
</span>from the right f(-2) = -(1/2)*(-2)+1 = 2
∴ The function is jump discontinues at -2
</span>
<span>Checking the <span>discontinuity at point 4
from the left f(4) = </span></span><span><span>-(1/2)*4+1 = -1
</span>from the right f(4) = -1
but there no equality in the equation so,
</span><span>∴ The function is discontinues at 4
The correct choice is the second
point </span>discontinuity at x = 4 and jump <span>discontinuity at x = -2</span>